Strategi Meningkatkan Kesiapan Guru dalam Implementasi Kurikulum Merdeka di SDN Pelambuan 2 - Muhammad Hafi Badali; Ahya Nabila; Diani Ayu Pratiwi; Aslamiah .; Chintya Adelya; Syaidati Elida (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The implementation of the Merdeka Curriculum in elementary schools still faces various challenges, particularly concerning teachers’ readiness to master subject content and utilize supporting learning technologies. This study aims to describe strategies to enhance teacher readiness in implementing the Merdeka Curriculum at SDN Pelambuan 2. This research employed a qualitative approach with a descriptive design. Data were collected through direct observation and in-depth interviews with two teachers directly involved in the curriculum implementation. The data analysis process included data reduction, data presentation, and drawing conclusions step by step to ensure valid and in-depth results. The findings indicate that teacher readiness at SDN Pelambuan 2 is relatively good, as shown by active discussion forums through the Teacher Working Group and the Subject Teacher Consultative Group, optimal use of the PMM/GTK platforms, and strong support from the principal. The strategies implemented include continuous training, strengthening digital literacy, and collaboration with external stakeholders to fully support the implementation of the Merdeka Curriculum.